Middle Meningeal Artery Embolization: What we Should Know (Bangladesh Journal of Neurosurgery, 2026)
Middle meningeal artery (MMA) embolization has emerged as an effective minimally invasive strategy in the  management of chronic subdural hematoma (cSDH), particularly in patients at high risk for surgical intervention or  with recurrent disease. Increasing evidence supports the concept that cSDH is a dynamic inflammatory process  driven by vascularized subdural membranes predominantly supplied by the MMA. Embolization of this artery  disrupts the pathological neovascular supply, promoting hematoma resorption and reducing recurrence rates. This  article provides a practical, beginner-oriented overview of MMA embolization, including indications, pathophysiological  rationale, relevant vascular anatomy, procedural steps, embolic materials, clinical outcomes, and potential  complications. Emphasis is placed on anatomical considerations and technical nuances essential for safe adoption  of the technique. As ongoing trials continue to refine patient selection and procedural protocols, MMA embolization  is poised to play an expanding role as both a primary and adjunctive therapy for chronic subdural hematoma.Bang. J Neurosurgery 2025; 14(2): 107-111